Toward an ethical framework for climate services: A White Paper of the Climate Services Partnership Working Group on Climate Services Ethics - Adams, P.; Eitland E; Hewitson B; Vaughan, Catherine; Wilby R; Zebiak, Stephen E. (2015)
This paper is intended to spur thinking and dialogue among the wide and relatively diverse community of actors engaged in practical activities surrounding the production, translation, transfer and use of climate information for societal decision making. This white paper is intended to start a conversation on ethics in the climate services community. To that end, the CSP Working Group on Climate Services Ethics is accepting comments on this white paper online at www.climate-services.org/ethics.